2012
DOI: 10.28945/1742
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Attitudes, Coping Strategies, and Achievement in Doctoral-Level Statistics Courses: A Mixed Research Study

Abstract: Because of the important role that attitudes toward statistics and motivation have played in statistics courses, Ramirez, Emmioglu, and Schau (2010) recently conceptualized that Eccles and Wigfield's (2002) Expectancy-Value Model (EVM) is applicable for students enrolled in statistics courses. However, to date, the applicability of the EVM for understanding students' attitudes toward statistics has not been tested empirically. Thus, the purpose of this mixed research study was twofold: (a) to build on Ramirez … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…The remaining percentage of 73% is based on factors that are not being chosen in the study. As a result, the unexplained factors should be considered in the upcoming research [23], [40]. Depending on the study mode, there was a significant difference in anxiety towards statistics.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining percentage of 73% is based on factors that are not being chosen in the study. As a result, the unexplained factors should be considered in the upcoming research [23], [40]. Depending on the study mode, there was a significant difference in anxiety towards statistics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers have studied doctoral students and how to improve attrition rates (Ali & Kohun, 2006;Gardner, 2009;Golde, 1998Golde, , 2005. Similarly, other researchers have sought to identify the challenges and coping mechanisms of doctoral students as well (Barnes & Randall, 2012;Combs & Onwuegbuzie, 2012;Gold, 2006;Martinez et al, 2013;Schlemper, 2011). The literature reviewed by the researchers indicated that there is still research needed on the topic of challenges and coping mechanisms necessary to the success of women doctoral students.…”
Section: Discussionmentioning
confidence: 99%
“…To collect data for this study, the researchers conducted three focus groups with 18 doctoral students who had recently been enrolled in a quantitative research methodology course. Combs and Onwuegbuzie (2012) identified peer support, requests for help, and positive self-motivation as coping strategies practiced by students when enrolled in a quantitative research methodology course.…”
Section: International Journal Of Educationmentioning
confidence: 99%
“…Leadership skills were important for students to interact productively with others in science due to its increasingly collaborative nature [ [ 39 , 40 , 41 ]]. Next were coping and interaction behaviours (stress management, conflict resolution) to alleviate tension [ [ 42 ]]. Lastly, teamwork skills were critical because idea sharing is encouraged in STEM [ [ 43 ]].…”
Section: Literature Reviewmentioning
confidence: 99%